Migration of optical excited states of the modified chromium complexes of collagen - Kumekov, S.E.; Saitova, N.K.; Syrgaliyev, E.O. (Ye.A.Buketov Karaganda State University Publishing house, 2017)
Photoluminescent properties of the collagen modified by chrome complexes are investigated. The analysis of the spectra of a photoluminescence at excitation in ultra-violet area shows that intrinsic photoluminescence of collagen undergoes a quenching with the increase of content of chromic complexes. In the modified collagen luminescence ranges are also deformed with full quenching of phenylalanine peak. The kinetics of decay of a photoluminescence of samples of the native and modified collagen, samples of phenylalanine and a tyrosine is measured. With the increase of content of chrome complexes in the modified collagen there is a redistribution of the dominating role of the radiating centers of collagen from the phenylalanine residue to tyrosine residue.
Keywords: photoluminescence; collagen; phenylalanine; tyrosine; chrome; quenching